La salud e higiene personal y su incidencia en el desarrollo físico, psicológico e intelectual de los niños y niñas de la escuela “Cesar Alonso Villacis Madrid” del barrio Collas Bajo, cantón Pujilì, periodo 2014 – 2015 - Achote Caiza, Silvia Marlene (2015)
Thisresearch is conductedat "Cesar AlonsoVillacisMadrid" school in which problems areevidenced, such as lackof hygiene inchildren. Theoretical and conceptualfoundations on healthand hygienefor children are framedand analyzed.It served assupportto havea solid foundationon the basicsforthe purpose.The current state ofcareand groomingthroughthe survey andthe interviewwere diagnosed, so the lackofparental careingroomingtheir childrenwas evidentand thisdoes notallowthe optimal development ofthem.Araining programfor farents inthe field ofhealth and hygieneweredesigned.The designof the purposeconsisted ofa characterization ofthe situationunder study, analysis and interpretation of surveys….